APOBEC3 genes: retroviral restriction factors to cancer drivers. Issue 5 (May 2015) - Henderson, Stephen; Fenton, Tim
Highlights APOBEC3 (A3) enzymes deaminate single-stranded DNA, mutating viral genomes. Tumors harbor mutations likely due to off-target A3 deamination of chromosomal DNA. A common APOBEC3 deletion polymorphism increases breast cancer risk. A growing body of evidence points to a driver role for APOBEC3s in tumorigenesis.